2022
DOI: 10.1038/s41467-022-30902-7
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of dolutegravir into an ultra-long-acting parenteral prodrug formulation

Abstract: Ultra-long-acting integrase strand transfer inhibitors were created by screening a library of monomeric and dimeric dolutegravir (DTG) prodrug nanoformulations. This led to an 18-carbon chain modified ester prodrug nanocrystal (coined NM2DTG) with the potential to sustain yearly dosing. Here, we show that the physiochemical and pharmacokinetic (PK) formulation properties facilitate slow drug release from tissue macrophage depot stores at the muscle injection site and adjacent lymphoid tissues following single … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…As widely reported for other disease areas, nanomedicine can overcome the limitations of the current PF therapies [52], [53]. Nanotherapies like nanoparticles, cellderived vesicles, nanopolymers are more amenable to modification to enhance their safety, specificity, and stimuli-responsive drug release [54], [55]. Additionally, there have been multiple reports of tailoring pharmacokinetics of drugs by using nanomedicinebased approaches [56].…”
Section: Current Status Of Covid-induced Pf Therapymentioning
confidence: 99%
“…As widely reported for other disease areas, nanomedicine can overcome the limitations of the current PF therapies [52], [53]. Nanotherapies like nanoparticles, cellderived vesicles, nanopolymers are more amenable to modification to enhance their safety, specificity, and stimuli-responsive drug release [54], [55]. Additionally, there have been multiple reports of tailoring pharmacokinetics of drugs by using nanomedicinebased approaches [56].…”
Section: Current Status Of Covid-induced Pf Therapymentioning
confidence: 99%
“…As widely reported for other disease areas, nanomedicine can overcome the limitations of the current PF therapies [ 52 , 53 ]. Nanotherapies such as nanoparticles, cell-derived vesicles, and nanopolymers are more amenable to modification to enhance their safety, specificity, and stimuli-responsive drug release [ 54 , 55 ]. Additionally, there have been multiple reports of tailoring the pharmacokinetics of drugs by using nanomedicine-based approaches [ 56 ].…”
Section: Current Status Of Covid-19-induced Pf Therapymentioning
confidence: 99%
“…The nanosuspension of VM1500A (deselsulfavirine; NNRTI), a parent drug of elsulfavirine [ 116 ], has been tested in a Phase 1 study, which demonstrated that a monthly injection was well tolerated and had an acceptable PK profile [ 117 ]. Gendelman et al developed CAB [ 70 ] and DTG [ 71 ] fatty acid prodrug-based LA injectable poloxamer nanocrystals [ 72 , 73 , 118 ]. CAB nanoformulations were tested in different animals and showed CAB plasma levels above the PA-IC 90 (~167 ng/ml) for up to a year [ 119 , 120 ].…”
Section: Approaches To Improving Existing Arvs For La Hiv Preventionmentioning
confidence: 99%